2005
DOI: 10.1103/physreva.71.023612
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion control for matter waves and gap solitons in optical superlattices

Abstract: We present a numerical study of dispersion manipulation and formation of matter-wave gap solitons in a Bose-Einstein condensate trapped in an optical superlattice. We demonstrate a method for controlled generation of matter-wave gap solitons in a stationary lattice by using an interference pattern of two condensate wavepackets, which mimics the structure of the gap soliton near the edge of a spectral band. The efficiency of this method is compared with that of gap soliton generation in a moving lattice recentl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
13

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 31 publications
0
40
0
13
Order By: Relevance
“…The BEC system considered here is loaded into a moving superlattice [42] consisting of primary and secondary moving optical lattices of the form…”
Section: Analytical Chaotic Solitonmentioning
confidence: 99%
“…The BEC system considered here is loaded into a moving superlattice [42] consisting of primary and secondary moving optical lattices of the form…”
Section: Analytical Chaotic Solitonmentioning
confidence: 99%
“…Theoretical interest in optical superlattices started only recently. Examples include work on fractional filling Mott insulator domains [20], dark [21] and gap [22] solitons, the Mott-Peierls transition [23], non-mean field effects [24] and phase diagrams of BEC in two-color superlattices [25]. Porter et al [26] have shown that optical superlattices can manipulate and control solitons in BEC.…”
Section: Introductionmentioning
confidence: 99%
“…The superlattice of Eq. (1) with γ = 2 has be widely studied [24]. In such a case, the X N (c 0 ) becomes…”
mentioning
confidence: 99%
“…The results suggest a feasible method for eliminating or strengthening chaos experimentally. Such a method can be extended to the controls of the spatial chaos with zero traveling velocity and the temporal chaos in other systems.Primary and secondary moving optical lattice compose the superlattice [24] as the formwhere we refer to V 1 cos 2 (kζ) as the primary lattice with V 1 and k corresponding to its depth and wave vector, and V 2 cos 2 (γkζ + φ) as the secondary one with V 2 being its depth, γ the ratio of the two laser wave vectors and φ the phase difference. The spatiotemporal variable ζ = x + v L t contains the velocity of the traveling lattice v L = δ/(2k) with δ being the frequency difference between the two counter-propagating laser beams producing the first lattice.…”
mentioning
confidence: 99%
See 1 more Smart Citation